2020
DOI: 10.1109/access.2020.2971834
|View full text |Cite
|
Sign up to set email alerts
|

D-GENE: Deferring the GENEration of Power Sets for Discovering Frequent Itemsets in Sparse Big Data

Abstract: Sparseness is the distinctive aspect of big data generated by numerous applications at present. Furthermore, several similar records exist in real-world sparse datasets. Based on Iterative Trimmed Transaction Lattice (ITTL), the recently proposed TRICE algorithm learns frequent itemsets efficiently from sparse datasets. TRICE stores alike transactions once, and eliminates the infrequent part of each distinct transaction afterward. However, removing the infrequent part of two or more distinct transactions may r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
10
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 74 publications
(58 reference statements)
0
10
0
Order By: Relevance
“…But the execution operation seems bit complex was the major drawback of this approach. Yasir et al 33 demonstrated the Deferring GENEration of Power sets (D‐GENE) that discovers frequent itemsets in sparse big data. Sparseness value, running time, number of transactions, minimum support were the evaluation metrics employed in this approach.…”
Section: Review Of Related Workmentioning
confidence: 99%
“…But the execution operation seems bit complex was the major drawback of this approach. Yasir et al 33 demonstrated the Deferring GENEration of Power sets (D‐GENE) that discovers frequent itemsets in sparse big data. Sparseness value, running time, number of transactions, minimum support were the evaluation metrics employed in this approach.…”
Section: Review Of Related Workmentioning
confidence: 99%
“…Recently, a new FIM algorithm, Deferring the Generation of Power sets for Mining Frequent Itemsets in Sparse Big data (D-GENE), was proposed [12]. D-GENE uses the concept of power set from set theory to generate an Iterative Trimmed Transaction Lattice (ITTL) of each transaction.…”
Section: Related Workmentioning
confidence: 99%
“…This section covers the working principle and the implementation details of the D-GENE algorithm for mining frequent co-occurring diseases [12]. In the first place, the detailed explanation of the dataset, preprocessing, and transformation steps is provided.…”
Section: Mining Frequent Co-occurring Diseasesmentioning
confidence: 99%
See 1 more Smart Citation
“…EAFIM [20] that uses the Apache Spark framework to achieve parallelism is an improved version of the apriori algorithm. Yasir, Muhammad, et al propose the HARPP [21], which adopt the concern of pow set and dictionary data structures, and the D-GENE [22], which suspends the process of ITTL generation till the completion of transaction pruning phase, discovering frequent itemsets from sparse datasets.…”
Section: Related Workmentioning
confidence: 99%